SAT0723-HPR Comparison of physical activity, fatigue, health-related quality of life, anxiety and depression between ankylosing spondylitis and rheumatoid arthritis patients. (12th June 2018) - Kinikli, G.I.; Yayla, M.E.; Ates, A.; Turgay, M.; Kinikli, G.
Abstract : Background: Rheumatoid arthritis (RA) and ankylosing spondylitis (AS) are chronic progressive inflammatory diseases, leading to joint damage and reducing the physical fitness of patients. They are among the most common rheumatic diseases. Physical inactivity, fatigue, low health-related quality of life (HRQoL), higher anxiety and depression levels are common problems reported in patients both ankylosing spondylitis (AS) and rheumatoid arthritis (RA) although the clinical manifestations differ in many ways. These low outcomes have been found to be associated with functional limitations in both AS and RA serves as mediators in the link between disease activity and functional limitations in spite of NSAIDs and DMARDs therapies. Although many studies have assessed the outcomes of a single disease state, either RA or AS, few studies have focused on a direct comparison between those both diagnostic groups. Objectives: The aim of this study to assess and compare physical activity, fatigue, HRQoL, anxiety and depression levels between AS and RA patients. Methods: Twenty-six RA patients and 18 patients with AS were recruited from the outpatient clinic. Physical activity was assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), a validated instrument comprising of four items that estimates the levels of vigorous activity, moderate activity, walking and time spent sitting during the previous 7 days. The Fatigue Severity Scale (FSS) was used to measure the severity of fatigue. Disease-specific instruments to measure (HRQoL) in patients with RA and AS (RAQoL and ASQoL) were used. The Hospital Anxiety and Depression Scale (HADS) were used to assess anxiety and depression. The patient groups were compared using the Kruskal-Wallis test and the Chi-square test. Results: Disease durations were similar between RA (mean age=48.92±12.50 years, disease duration=10.81±7.68 years) and AS (mean age=43.44±12.36 years, disease duration=11.39±8.87 years) patients (p=0.867). There was no statistically difference between FSS (RA=45.27±16.95; AS=41.00±12.95; p=0.173), IPAQ-SF (RA=1289.65±839.75; AS=2110.06±1210.86; p=0.062) and HADS scores (RA=18.31±2.93; AS=17.00±2.87; p=0.123) in both patient groups. Conclusions: Our results support that physical inactivity due to impaired mobility as well as fatigue, anxiety/depression and low (HRQoL) are common and similar features of both RA and AS. In conclusion, management of disease activity with drug therapies should be targeted not only to improve physical function for RA and AS but also to improve physical activity levels, restore fatigue, anxiety and depression levels and preserve HRQoL. References: [1] Lie E, Kristensen LE, Forsblad-d'Elia H, Zverkova-Sandström T, Askling J, Jacobsson LT, et al. The effect of comedication with conventional synthetic disease modifying antirheumatic drugs on TNF inhibitor drug survival in patients with ankylosing spondylitis and undifferentiated spondyloarthritis: results from a nationwide prospective study. Ann Rheum Dis2015;74:970–8. [2] Iannone F, Lopalco G, Rigante D, Orlando I, Cantarini LG. LapadulaImpact of obesity on the clinical outcome of rheumatologic patients in biotherapy Autoimmun Rev2016;15:447–450. Disclosure of Interest: None declared